(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article will study the role and effectiveness of modern technologies in teaching English. Based on literature analysis, the impact of various technological tools on the language learning process, their advantages and limitations are discussed. The results show that modern technology is important in Language Teaching, but their effective application depends on teacher skills and integration into curricula. The article will analyze promising areas of use of technology and existing problems.